Predictive and adaptive extremal control - Kimmel, Ivriani (Department of Electrical Engineering, 2015)
The time-optimal predictive control strategy for second order relay or bang-bang control systems is investigated along with modifications of this strategy for third order systems. One basis of this strategy is the utilization of a model, a replica of the plant, run in a fast-time mode so as to obtain the future output of the plant under the present input. Based upon these measurements, corrections to the plant may be implemented to achieve the desired response. The concept of the fast model is a useful one in that it falls into the synthesis of the more general time-optimal trajectory and switching functions for various second, third and higher order plants. However the difficulties in providing the exact time-optimal control for these plants result in the generation of acceptable sub-optimal and near time-optimal strategies. The nature of plant sensitivity, parameter variation and identification are investigated as well as a novel self-adoptive controller which dispenses with the identification phase but identifies a certain surface in the state space and establishes a stable sub-optimal control strategy. These control techniques are applied to a small DC motor with responses close to time-optimal.